Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Pacific Southwest)--Brown rock crab, red rock crab, and yellow crab - Carroll, Jay C.; Winn, Richard N. (Washington, D.C. U.S. Department of the Interior, 1989)
U. S. Fish and Wildlife Service. Biological report ; 82(11.117)
Keywords: Yellow crab--Pacific Southwest; Red rock crab; Brown rock crab